2012
DOI: 10.1002/lary.22508
|View full text |Cite
|
Sign up to set email alerts
|

Adenotonsillar hypertrophy: Correlation between obstruction types and cardiopulmonary complications

Abstract: Patients with adenoid and tonsil hypertrophy are at a higher risk for cardiopulmonary complications, poorer quality of life, and more severe UAO symptoms and should have priority for surgical treatment to prevent cardiopulmonary complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 25 publications
0
32
0
1
Order By: Relevance
“…In a recent study by Tatlipinar et al (17) showed that mean pulmonary artery pressure and right ventricle myocardial performance index were higher in patients with adenoid hypertrophy and adenoid and tonsil hypertrophy in comparison with the normal group. Also, Koc et al (15) demonstrated that adenotonsillectomy improved right ventricle performance and reduced mean pulmonary artery pressure in children with adenotonsillar hypertrophy.…”
Section: Discussionmentioning
confidence: 94%
“…In a recent study by Tatlipinar et al (17) showed that mean pulmonary artery pressure and right ventricle myocardial performance index were higher in patients with adenoid hypertrophy and adenoid and tonsil hypertrophy in comparison with the normal group. Also, Koc et al (15) demonstrated that adenotonsillectomy improved right ventricle performance and reduced mean pulmonary artery pressure in children with adenotonsillar hypertrophy.…”
Section: Discussionmentioning
confidence: 94%
“…A previous study demonstrated that the size of both the adenoid and tonsil was significantly correlated with OSA and cardiopulmonary complications 16 , 17) . Therefore, we selected patients with grades III-IV of ATH confirmed using the method of Cohen and Konak and the Brodsky scale.…”
Section: Discussionmentioning
confidence: 98%
“…33 Although several studies have reported that adenotonsillar size does not reliably predict SBD, many clinicians still use ATH as a clinical indicator for SDB in children. 34 So, in this study, we tried to investigate the association among sAA activity, OSA severity, and ATH (tonsil size and AN ratio) in children.…”
Section: Discussionmentioning
confidence: 99%